2004
DOI: 10.1113/expphysiol.2004.027656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metabolic cage housing on immunoglobulin A and corticosterone excretion in faeces and urine of young male rats

Abstract: Six 8-week-old Sprague-Dawley rats were studied for 9 days divided into three periods of 3 days each: before transferral to metabolism cages, during metabolic cage housing and after return to their home cages. Faeces were collected daily when the animals were housed in their home cages and every 6 h when the animals were housed in metabolic cages during which time urine was also collected every 6 h. The rate of weight gain was slightly reduced during the 3 days in metabolic cages and the animals produced signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 27 publications
4
56
1
Order By: Relevance
“…The Cryptochrome (Cry) and Clock genes are proposed to be part of the core clock as well as the Per genes (Albrecht 2004), which suggests that the corticosterone rhythm might, to some degree, be dependent on a fully functional clock. It might be argued that the metabolic cage represents a stressor for the mice as it has been shown to be the case for rats (Eriksson et al 2004). In order to avoid such an effect, the habituation period of 4 days was chosen even 1 day longer than previously shown as affective (Touma et al 2004).…”
Section: Glucose Tolerance Testmentioning
confidence: 99%
“…The Cryptochrome (Cry) and Clock genes are proposed to be part of the core clock as well as the Per genes (Albrecht 2004), which suggests that the corticosterone rhythm might, to some degree, be dependent on a fully functional clock. It might be argued that the metabolic cage represents a stressor for the mice as it has been shown to be the case for rats (Eriksson et al 2004). In order to avoid such an effect, the habituation period of 4 days was chosen even 1 day longer than previously shown as affective (Touma et al 2004).…”
Section: Glucose Tolerance Testmentioning
confidence: 99%
“…24,[30][31][32][33][34][35][36][37][38] This modification exerted only a limited impact on the biokinetics of PAA-PEG and PAA NPs since most of these NPs in the brain were in residual blood. However, in contrast, the amounts of gold and TiO 2 NPs in the brain cannot be explained by differences in the content of residual blood, which lends support to a permeability greater than zero.…”
mentioning
confidence: 99%
“…The amount of radioactivity detected in feces was highest and displayed a more pronounced peak 12h after injection when the substance was administered through a jugular vein catheter than through tail vein injection. As expected, it is evident that there were great differences in the profiles of radioactive excretion among individuals in rodents, particularly in well studied species such rats and mice, as in others mammals (Brown et al, 1994;Palme et al, 1996), i.e., time course may change with the route and time of administration, even between sexes in some species (see detailed studies on rats: Touma et al, 2003;Eriksson et al, 2004;Abelson et al, 2009). Similarly, in chinchilla, Busso et al (2005a also indicated that radioactive urinary estradiol peaked between 24-48h, the radioactive peak being at 34h post-infusion.…”
Section: Sciurognathi (Squirrel and Mouse-like Forms)mentioning
confidence: 93%